Loser66
  • Loser66
Make it clear, please. I confused. How to turn it to i = 0 \(\sum_{i=1}^n a^i\) to \(\sum_{i=0}^{??}\) Please, help
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
\[\sum_{i=0}^{n}(i)^(n-1)\]
Loser66
  • Loser66
I was taught that when we replace i =1 from i =0, whenever I saw i, subtract 1 Hence the lower limit is i=0, the summand is \(a^{n-1} \) . How about the upper limit?
Loser66
  • Loser66
@AliLnn cannot be n as it is on original one. :(

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

Loser66
  • Loser66
sorry, *\(a^{i-1}\)
Loser66
  • Loser66
Ex: \(\sum_{i=1}^5 i =1 +2+3+4+5\) when I turn it to i =0, the sum must be \(\sum_{i=0}^6 i = 0 +1+2+3+4+5\) to make it the same with the original one, right?
Loser66
  • Loser66
At that moment , the upper limit is n +1, not n-1, That makes me confused
ganeshie8
  • ganeshie8
\(\sum_{i=1}^n a^i\) Let \(j=i-1\) : \(i=1\implies j=0\) \(i=n\implies j=?\)
Loser66
  • Loser66
@ganeshie8 j = n-1, but how to argue for my example above?
Empty
  • Empty
\[\sum_{i=1}^{i=n} a^i\] You want the lower bound to be 0, so we do algebra on the bottom part since it is but a simple equation! \[\sum_{i-1=0}^{i=n} a^i\] Now we see our substitution clearly: \[i-1=j\] Rearrange this to plug in our new value everywhere: \[i=j+1\] Goes in: \[\sum_{i-1=0}^{i=n} a^i=\sum_{j=0}^{j+1=n} a^{j+1}=\sum_{j=0}^{j=n-1} a^{j+1}\] This is what you must do and nothing more, it is just tiny equations on top of and below a funny greek letter. :P
ganeshie8
  • ganeshie8
your example just happens to be a special case : 0 + anything = anything that doesn't mean, we don't have two terms on the left hand side.
ganeshie8
  • ganeshie8
maybe try contrasting below two identical sums : \(\sum\limits_{i=1}^6e^i\) and \(\sum\limits_{i=0}^5e^{i+1}\)
Loser66
  • Loser66
Ex2: \(\sum_{i=1}^5 3i^2=3\sum_{i=1}^5 i^2 =3(1^2+2^2+3^2+4^2+5^2)\) the first element is 3, the last one is 75 If I want to turn it from 0 to ?? the sum must stay as it is. right?\(\sum_{i =0 }^4 3(i^2) = 3(0^2+ 1^2+2^2+3^2 +4^2)\) Surely, the sum doesn't stay as it is. :(
ganeshie8
  • ganeshie8
I see, you must do the substitution inside also. : \(\sum_{i=1}^5 3i^2=3\sum_{i=1}^5 i^2 =3(1^2+2^2+3^2+4^2+5^2)\) substitute \(j=i-1\), the sum is same as : \(\sum_{j=1-1}^{5-1} 3(j+1)^2=3\sum_{j=0}^4 (j+1)^2 =3(1^2+2^2+3^2+4^2+5^2)\)
ganeshie8
  • ganeshie8
Notice that both the series are one and same and they match term by term
Loser66
  • Loser66
Got this part :) Now other example
Loser66
  • Loser66
\(\sum_{i =1}^5 3^i\)
ganeshie8
  • ganeshie8
\(\sum_{i =1}^5 3^i\) substitute \(j=i-1\), the sum can be rewritten as \(\sum_{j =1-1}^{5-1} 3^{j+1}\)
Loser66
  • Loser66
Thank you so so much. I got it now. :)

Looking for something else?

Not the answer you are looking for? Search for more explanations.